Dabigatran deliberate overdose: two cases and suggestions for laboratory monitoring. (15th March 2016) - Vlad, Ioana; Armstrong, Jason; Ridgley, James; Pascu, Ovidiu
Abstract: Context : Dabigatran etexilate (dabigatran) is a direct thrombin inhibitor anticoagulant agent. There is limited information about the changes in coagulation profile and outcomes in overdose. A monoclonal antibody has been developed to neutralize the anticoagulant effect of dabigatran. Case reports describe enhanced clearance of dabigatran by haemodialysis as an intervention to prevent haemorrhagic complications – however, the threshold for initiating haemodialysis is not well defined in an asymptomatic patient with normal renal function.Case details : Two patients presented following deliberate dabigatran overdoses. A 55-year-old woman ingested 10 × 150 mg dabigatran. A 21-year-old woman with a history of systemic lupus erythematosus and pulmonary embolus ingested 100 × 110 mg dabigatran. Both were admitted to the intensive care unit and managed expectantly. Serial coagulation tests normalized over 60 h. The half-life of dabigatran was not prolonged following overdose, being calculated between 7 and 11 h in each case. There was positive correlation between international normalized ratio (INR), prothrombin time (PT) and activated partial thromboplastin time (aPTT) with plasma dabigatran levels.Conclusion : There is limited experience with dabigatran overdoses. Normal aPTT, PT and INR assays 12 h following deliberate ingestion indicate that the drug concentration is not high. Individual risk assessment of bleeding risk needs to be formulated for each patient and expectant management is reasonable in the presence of normal renal function and absent risk factors for bleeding.